The new treatment of the capacity regime in the Peruvian Civil Code - Varsi-Rospigliosi, Enrique; Torres Maldonado, Marco Andrei (Acta Bioethica, 2019)
Peru has a new capacity treatment in the Civil Code of 1984, achieving an approach to the guidelines of the United Nations in favor of the autonomy and full legal capacity of persons with disabilities. Through the latest modifications made by Legislative Decree N. 1384, several unfinished aspects are linked to the rights of persons with disabilities based on respect for the human rights of all citizens, especially in terms of their dignity, autonomy and equality before the law. The current social model replaces the regime of substitution of the will of the incapable by one of assistance through the so-called supports and safeguards. Every person, regardless of their capacity, is a subject of free right to take and respond to their personal decisions.